The coastal marine Tardigrada of the Americas - Miller, William R.; Perry, Emma S. (Zootaxa, 2016)
The Western Hemisphere or the New World, also known as the Americas (North, Central and South America, associated islands and included seas) have historically been divided into two Realms, the Nearctic and Neotropical based on terrestrial biogeography. The coasts of these two terrestrial realms are bordered by six marine realms, 14 marine provinces and 67 marine ecoregions. From current literature, a comprehensive list of the marine tardigrade fauna from the Americas is presented. Data on marine tardigrades were obtained from 385 published Records of the Occurrence (RoO) of a species, their location, tidal zone, and the substrates from which they were reported. Authors’ identifications were accepted at face value unless subsequently amended. Thirty genera and 82 species or subspecies are reported from the Americas; 49 species are documented from margins of the terrestrial Nearctic realm (North America) and 48 from terrestrial Neotropical realm (South America) with only 17 species occurring in both. We define cosmopolitan distribution for marine tardigrades as occurring in or on the margins of five of the seven oceans, only two species of marine tardigrade meets this standard. From the Americas 39 species have been described as new to science, 32 species appear restricted to the hemisphere. Taxa were assigned to marine ecoregions based on adjacent geopolitical units (country, states, provinces, etc.) described in published records. Although tardigrades have been reported from all six marine realms, they are only known from 21 of the 67 ecoregions. Most marine tardigrade sampling in the Americas has focused on near shore substrate (sand, mud, barnacles); for some species no substrates have been reported. The west coasts of both continents have little or no data about tardigrade presence.